On the Economic Theory of Socialism: Part Two - Lange, Oskar (Review of Economic Studies, 1937)
Journal Article On the Economic Theory of Socialism: Part Two Oskar Lange Oskar Lange London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 4, Issue 2, February 1937, Pages 123–142, https://doi.org/10.2307/2967609 Published: 01 February 1937